Discovery of potent, orally bioavailable in vivo efficacious antagonists of the TLR7/8 pathway. Issue 17 (1st September 2020) - Alper, Phil B.; Deane, Jonathan; Betschart, Claudia; Buffet, David; Collignon Zipfel, Géraldine; Gordon, Perry; Hampton, Janice; Hawtin, Stuart; Ibanez, Maureen; Jiang, Tao; Junt, Tobias; Knoepfel, Thomas; et al.
Graphical abstract: Abstract: Antagonism of the Toll-like receptors (TLRs) 7 and TLR8 has been hypothesized to be beneficial to patients suffering from autoimmune conditions. A phenotypic screen for small molecule antagonists of TLR7/8 was carried out in a murine P4H1 cell line. Compound 1 was identified as a hit that showed antagonistic activity on TLR7 and TLR8 but not TLR9, as shown on human peripheral blood mononuclear cells (hPBMCs). It was functionally cross reactive with mouse TLR7 but lacked oral exposure and had only modest potency. Chemical optimization resulted in 2, which showed in vivo efficacy following intraperitoneal administration. Further optimization resulted in 8 which had excellent in vitro activity, exposure and in vivo activity. Additional work to improve physical properties resulted in 15, an advanced lead that had favorable in vitro and exposure properties. It was further demonstrated that activity of the series tracked with binding to the extracellular domain of TLR7 implicating that the target of this series are endosomal TLRs rather than downstream signaling pathways.